2010
DOI: 10.3174/ajnr.a2289
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the Mid-Cingulate Cortex in Amyotrophic Lateral Sclerosis Detected In Vivo with MR Spectroscopy

Abstract: BACKGROUND AND PURPOSE:Various lines of evidence implicate cerebral involvement beyond the motor cortex in ALS, including the cingulate gyrus and the thalamus. The purpose of this study was to assess neurodegeneration in these regions in vivo by using MRSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
6
17
0
Order By: Relevance
“…Furthermore, a decrease in tNA was associated with a decrease in forced vital capacity, another measure of disease progression. A number of studies have also explored correlations between tNA and clinical scales, and have reported significant associations among tNA levels and ALSFRS-R scores [12, 17, 41], UMNB burden scores [16, 17, 41], and rate of disease progression [42]. Thus, our study confirms the importance of NAA as reliable biomarker for neuronal injury and disease progression.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, a decrease in tNA was associated with a decrease in forced vital capacity, another measure of disease progression. A number of studies have also explored correlations between tNA and clinical scales, and have reported significant associations among tNA levels and ALSFRS-R scores [12, 17, 41], UMNB burden scores [16, 17, 41], and rate of disease progression [42]. Thus, our study confirms the importance of NAA as reliable biomarker for neuronal injury and disease progression.…”
Section: Resultssupporting
confidence: 83%
“…39 A number of studies have also explored correlations between NAA and clinical scales, and have reported significant associations between NAA levels and revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) scores, 37,38,47,51 UMN disease burden, 37,44,52 Norris Scale scores, 36,42 finger-tapping rate, 38 hand strength, 38 disease duration, 47 and rate of disease progression. 34 Taken together, these results point to a reduction in neuronal integrity in the motor cortex in ALS.…”
Section: Advanced Neuroimaging In Alsmentioning
confidence: 81%
“…3446 Evidence is conflicting as to whether these changes occur early in clinically evident disease: one study reported decreases in NAA:Cr ratios at a mean disease duration of 6.5 months, 47 whereas another study reported no significant differences in NAA levels in patients diagnosed with ALS within the past year. 48 …”
Section: Advanced Neuroimaging In Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is consistent with previous studies using advance brain imaging techniques that showed decreased activity in various brain regions, including the thalamus in ALS patients. [29][30][31][32][33][34] Considering that a number of thalamic nuclei project their axons to motor cortical areas, 35 alteration of thalamic network activity caused by ALS-associated mutations may alter the electrical input received by motor neuronal structures, which may eventually cause an alteration of motor movement control. Alteration in T-type channel resulting in a loss of function can also alter the balance between excitatory and inhibitory neuronal networks.…”
Section: Discussionmentioning
confidence: 99%